Reproductive phenology of Atlantic forest tree species in Brazil: An eleven year study - Engel, Vera Lex [UNESP]; Martins, Fernando Roberto (My University, 2005)
This paper describes the reproductive phenorhythms of tree species in a tropical seasonal lowland forest in Southeastern Brazil. Every two weeks, five individuals of 41 species were observed for the occurrence of flowering and fruiting, from May 1982 to December 1992. All phenophases showed high seasonality, when considering the whole set of species, but the amplitude of the cycles was much more variable between years; only 13 species had regular flowering. Infra-annual flowering and fruiting were found in 11 and four species, respectively, while only one species flowered and fruited continually. Supra-annual cycles were observed in four (flowering) and seven (fruiting) species. An increase was observed in number of species and individuals flowering and fruiting from 1990 to 1992, following mainly an elevation in the absolute minimum air temperature. These data suggest a relationship between reproductive phenology and major climatic phenomena like El Niño events and solar activity cycles. © International Society for Tropical Ecology.
Keywords: Atlantic forest; El Niño; Reproductive phenology; Seasonality; Tropical tree species; El Nino; phenology; reproductive biology; seasonality; solar cycle; tree; Brazil; South America